Inhibiting cardiac myeloperoxidase alleviates the relaxation defect in hypertrophic cardiomyocytes. Issue 2 (11th March 2021) - Ramachandra, Chrishan J A; Kp, Myu Mai Ja; Chua, Jasper; Hernandez-Resendiz, Sauri; Liehn, Elisa A; Knöll, Ralph; Gan, Li-Ming; Michaëlsson, Erik; Jonsson, Malin K B; Ryden-Markinhuhta, Katarina; Bhat, Ratan V; Fritsche-Danielson, Regina; et al.
Abstract: Aims: Hypertrophic cardiomyopathy (HCM) is characterized by cardiomyocyte hypertrophy and disarray, and myocardial stiffness due to interstitial fibrosis, which result in impaired left ventricular filling and diastolic dysfunction. The latter manifests as exercise intolerance, angina, and dyspnoea. There is currently no specific treatment for improving diastolic function in HCM. Here, we investigated whether myeloperoxidase (MPO) is expressed in cardiomyocytes and provides a novel therapeutic target for alleviating diastolic dysfunction in HCM. Methods and results: Human cardiomyocytes derived from control-induced pluripotent stem cells (iPSC-CMs) were shown to express MPO, with MPO levels being increased in iPSC-CMs generated from two HCM patients harbouring sarcomeric mutations in the MYBPC3 and MYH7 genes. The presence of cardiomyocyte MPO was associated with higher chlorination and peroxidation activity, increased levels of 3-chlorotyrosine-modified cardiac myosin binding protein-C (MYBPC3), attenuated phosphorylation of MYBPC3 at Ser-282, perturbed calcium signalling, and impaired cardiomyocyte relaxation. Interestingly, treatment with the MPO inhibitor, AZD5904, reduced 3-chlorotyrosine-modified MYBPC3 levels, restored MYBPC3 phosphorylation, and alleviated the calcium signalling and relaxation defects. Finally, we found that MPO protein was expressed in healthy adult murine and human cardiomyocytes, and MPO levels were increased in diseased hearts with left ventricular hypertrophy. Conclusion: This study demonstrates that MPO inhibition alleviates the relaxation defect in hypertrophic iPSC-CMs through MYBPC3 phosphorylation. These findings highlight cardiomyocyte MPO as a novel therapeutic target for improving myocardial relaxation associated with HCM, a treatment strategy which can be readily investigated in the clinical setting, given that MPO inhibitors are already available for clinical testing. Graphical Abstract: